Kesehatan Bank Syariah Indonesia: Studi Komparasi Bank Syariah Indonesia Pra dan Pasca Merger - Sya'bania, Indah; Haryono, Haryono; Yunita, Khristina (Politeknik Negeri Medan, 2024)
The purpose of this study is to evaluate and contrast Bank Syariah Indonesia's (BSI) state before and after a merger. Using non-performing financing (NPF), financing to deposit ratio (FDR), good corporate governance (GCG), return on asset (ROA), operating costs and operating income (BOPO), and capital adequacy ratio (CAR) as measurement indicators, this research was carried out using the RGEC (risk profile, good corporate governance, earnings, & capital) method. In this study, the Paired Sample T-test was used in a comparative analysis with the results of FDR, GCG, and CAR showing no significant differences, the data showed substantial differences in NPF, ROA, and BOPO. Following the merger, BSI's overall health can be described as